A Review On Vishakta Ahara And Its Management Through Agad Tantra Principles - Sayali Kulkarni; Nikita V. Naik; Shweta Mumbaraddi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Vishakta Ahara, or contaminated food, is a significant concern in Ayurveda, particularly under the domain of Agad Tantra—the branch of Ayurvedic toxicology. Contamination may arise due to microbial spoilage, chemical adulteration, improper storage, or natural toxins. Classical texts describe how the consumption of such impure food can vitiate Doshas and lead to Vishavikara (toxic disorders). These descriptions align with the modern concepts of food poisoning and foodborne illnesses. Ancient seers have elaborated detailed classifications, symptoms, and management strategies for Vishakta Ahara, emphasizing both prevention and treatment. Aim: To critically review the Ayurvedic concept of Vishakta Ahara and evaluate its management through the principles of Agad Tantra in correlation with modern toxicological approaches. Objectives: To explore classical Ayurvedic references and definitions of Vishakta Ahara.To identify the etiological factors and clinical manifestations associated with Vishakta Ahara.To analyze the treatment modalities described in Agad Tantra for managing food toxicity.To correlate Ayurvedic understanding of Vishakta Ahara with modern concepts of foodborne illnesses. Materials and Methods: A thorough literary review was conducted from classical Ayurvedic texts such as Charaka Samhita, Sushruta Samhita, AshtangaHridaya, and Kashyapa Samhita. Supplementary data were collected from modern scientific journals and recent research on foodborne illnesses. Comparative analysis was done between the classical description of Vishakta Ahara and contemporary toxicology. Results: Ayurvedic literature classifies Vishakta Ahara based on origin, cause of contamination, and spoilage. Common symptoms include gastrointestinal discomfort, systemic reactions, and severe toxicity. Management strategies described in Agad Tantra include administration of Agada (antidotes), therapeutic measures like Vamana (emesis), Virechana (purgation), and use of Deepana-Pachana (digestive and metabolic stimulants). Specific formulations such as MahagandhakaAgada and VishaghnaDravyas like Haridra and Triphala are recommended for detoxification and symptom alleviation. Conclusion:The concept of Vishakta Ahara in Ayurveda is highly relevant in addressing modern foodborne illnesses. The management approach through Agad Tantra not only focuses on treatment but also emphasizes preventive measures. Such integrative understanding can contribute significantly to contemporary public health, especially in the context of rising food adulteration.